Community Behavior and Response in Educating The Implementation of Health Protocols In Public Places During The New Normal Period - Ikhsan Ibrahim; Rollina Ahmad; Fitri Hayati; Hery Sahputra; Nurhayati Nurhayati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
The community has an important role in breaking the chain of transmission of COVID-19 so as not to cause new sources of transmission/clusters in places where the movement of people, the interaction between humans, and large gatherings of people occurs. The community must be able to carry out activities again in the COVID-19 pandemic situation by adapting to new habits that are healthier, cleaner, and more obedient, which are implemented by all components in the community and empower all existing resources. The community's role in breaking the chain of transmission of COVID-19 (the risk of contracting and transmitting it) must be done by implementing health protocols. To provide an overview of the behavior and response of the community to implement health protocols by the Covid-19 Education Team in public places during the New Normal era in the city of Dumai. This study is research with a qualitative approach. The data used in this study is to use observation which sees and directly observes people's behavior in the field and also takes some data online due to situations that require social distancing. This research was carried out in several public places, including the task stations of the Dumai City Covid-19 Education Team, which began in June-July 2020. The research subjects were the sources of data observed by the research problem. In general, the behavior and response of the community to the implementation of health protocols during the New Normal period in public places by the Covid-19 Education Team could have been better. Moreover, several factors cause this, namely education, knowledge, and the community's economy. As well as developing issues, public confidence decreases about the dangers of the Covid-19 virus. The educational activities provided will only be meaningful if there is compliance and mutual community support.